1977
DOI: 10.1002/cne.901710107
|View full text |Cite
|
Sign up to set email alerts
|

The efferent connections of the feline nucleus cuneatus

Abstract: Nucleus cuneatus projections to nucleus ventralis posterolarteralis pars medialis (VPLm) and other thalamic as well as midbrain and medullary nuclei were studied in cats using the Fink-Heimer I silver technique. Single electrolytic lesions of very small size were made stereotaxically in different zones of nucleus cuneatus under electrophysiological control. All zones studied projected to contralateral VPLm in a pattern of discrete terminal arborizations or clusters, which were organized in onionskin-like dorso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0

Year Published

1981
1981
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(41 citation statements)
references
References 66 publications
3
38
0
Order By: Relevance
“…Furthermore, in agreement with previous physiological studies (MASSION, 1961;NISHIOKA and NAKAHAMA, 1973;ECCLES et al, 1975b), there are peripheral inputs to RN which are not mediated by the cerebellum or cerebral cortex. Our result has shown that ML is the monosynaptic input to RN thus corroborating previous histological and physiological studies (CAJAL, 1909(CAJAL, -1911HAZLETT et al, 1972;HAND and LIU, 1966;PADEL and JENESKOG, 1981;Padel, personal communication;Fanardyan, personal communication).…”
Section: Discussionsupporting
confidence: 80%
“…Furthermore, in agreement with previous physiological studies (MASSION, 1961;NISHIOKA and NAKAHAMA, 1973;ECCLES et al, 1975b), there are peripheral inputs to RN which are not mediated by the cerebellum or cerebral cortex. Our result has shown that ML is the monosynaptic input to RN thus corroborating previous histological and physiological studies (CAJAL, 1909(CAJAL, -1911HAZLETT et al, 1972;HAND and LIU, 1966;PADEL and JENESKOG, 1981;Padel, personal communication;Fanardyan, personal communication).…”
Section: Discussionsupporting
confidence: 80%
“…Overall, the afferent connectional pattern to the teleost TSe is quite similar to that of the intercollicular nucleus in amniotes, as suggested by Muñoz et al (1997). An alternative interpretation, however, is that the teleost TSe corresponds to the same-named toral nucleus in mammals receiving fibers from the spinal trigeminal nucleus, nucleus X, dorsal column nuclei, and spinal cord (Hand and Winkle, 1977;Aitkin et al, 1981;Coleman and Clerici, 1987;Li and Mizuno, 1997) and to the somatosensory receptive toral zone in other vertebrates (birds: Wild, 1989;amphibians: Muñoz et al, 1997).…”
Section: External Toral Nucleusmentioning
confidence: 68%
“…A compa rable finding has been reported for the cat [Cheeket al, 1975] and rat [Lund and Web ster, 1967]. Rather, most of those cells ap pear to innervate extrathalamic regions such as the cerebellum (the opossum, pres ent investigation; the cat, Rinvik and Walberg, 1975;Cheek et al, 1975), the inferior olive (the cat, Berkley, 1975;Berkley and Hand, 1976;Hand and Van Winkle, 1977;Boesten and Voogd, 1975;Groenwegen et al, 1975], the spinal cord (the opossum, Crutcher et al, 1978, and present study; the cat, rat and monkey, Burton and Loewy, 1977), as well as various brain stem nuclei (the cat, Lund and Webster, 1967;Hand and Van Winkle, 1977).…”
Section: Projections To the Thalamusmentioning
confidence: 88%